Efficient water management system in pharmaceutical manufacturing premises / Kugaanesaan Murthy - Kugaanesaan, Murthy (2018)
Main source of drinking water supply in Malaysia is surface water stored in reservoirs. High operation and maintenance cost as well as environmental impacts are identified due to lack of sustainable sewage industry. Past studies have shown that water consumption in pharmaceutical industry is high due to high quality treated water requirement for the processes involved in the industry which led to high waste water generation and difficulty in treating the waste water. This study aimed to understand the water requirement for consumption in pharmaceutical manufacturing premises and identify possible solutions for reduction of water usage as well as reduce waste water generation from the processes involved. This study was carried out in a pharmaceutical manufacturing plant located in Peninsular Malaysia. Reverse Osmosis (RO) is one of the common water purififcation system in pharmaceutical industry which utilizes natural water osmosis phenomenon in reverse in order to produce purified water. Energy recovery devices are devices to recover the pressure energy from the reject stream and reuse it back in the process as the reject stream has a signifiant amount of energy resulted from high pressure and low recovery characteristic of Reverse Osmosis system. The Energy Recovery Device chosen was the Pressure Exchanger which was found was found to recover 28% of the high-pressure pump work, achieving annual savings of approximately 9800 kWh for the site at assumed 98% efficiency. Water recycling is reusing water for beneficial purposes such as agricultural and landscape irrigation, industrial processes, toilet flushing, and replenishing a ground water basin (referred to as ground water recharge) which offers resource and financial savings. The common water recycling is recycling of treated wastewater as the discharge is controlled at pharmaceutical industry. Overall high water consumption identified at site and average about 50 m3/day of treated water being discharged daily to the perimeter drain found to be useful if reused for other that drinking water usage which could save water consumption and the cost involved. Treated water can be used for purposes such as gardening, external area cleaning, toilet flushing, Chiller make up water, and cooling of ambient temperature of chiller units. Reusing treated water can reduce water consumption at site and treated water discharge could be recycled which will reduce the discharge to the surrounding. Hence, less impact to the environment and better management of natural resources at site. This research can be extended in more depth in terms of the process optimisation as in the manufacturing processes as this current research is about reducing and controlling the existing system energy consumption which does not impact the manufacturing processes.